Total synthesis of (+)-grandiamide D, dasyclamide and gigantamide A from a Baylis–Hillman adduct: A unified biomimetic approach - Ilangovan, Andivelu; Saravanakumar, Shanmugasundar (Beilstein Journal of Organic Chemistry, 2014)
A unified strategy was followed for the synthesis of three putrescine bisamides, (+)-grandiamide D, dasyclamide and gigantamide A, isolated from leaves of Aglaia gigantea, by making use of a common synthetic intermediate prepared by the Baylis–Hillman reaction. Asymmetric synthesis of the natural (+)-grandiamide D was accomplished from camphor sultam.
Keywords: Baylis–Hillman reaction; dasyclamide; gigantamide A; (+)-grandiamide D; natural products; putrescine bisamides